Enzymatic rettings of green pepper berries for white pepper production - Shamsudin, Rosnah; Chan, Shiang Chun (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
This study is carried out to determine the physical properties of green pepper berries and to improve the existing retting technique in white pepper production using the Viscozyme and Celluclast as the enzymes. Effects of blanched and non-blanched pepper berries, acidic solution and non-acidic solution, and different temperature of 28, 35, 42, and 49°C are determined to obtain the optimum conditions for enzymatic retting. The physical properties of green pepper berries such as dimension (5.21 mm), weight (0.11 g per berry), true density (1319.33 kg/m3), bulk density (596.9 kg/m3), sphericity (0.976), angle of repose (6.87°) and flow ability with funnel flow time of 5.27 seconds were determined. The enzymatic retting in 42oC can fully soften the pericarp of pepper berries from 15 days to 7 days. The enzymatic decortication has the efficiency in acidic solution (pH 4) and temperature of 42°C with non-blanched pepper berries. The enzymatic retting reached constant fracture force (20.98N) at the ninth soaking days while the non-enzymatic retting reached constant fracture force (21.89N) at the fifteenth soaking days.